Saber por experimentar: Biography of “La poesía gauchesca” (1931-1957) by Jorge Luis Borges (2020)
The aim of this article is inquiring Jorge Luis Borges’ “La poesía gauchesca” essayistic procedures empha- sizing the essay as a form, the problem of the beginnings, and its writing maneuvers.The works of Alberto Giordano (2005, 2015, 2017), Julio Premat (2012), and Annick Louis (2014) have been consulted as theoretic frame of reference for the mentioned topics. In addition, it was performed a comparative reading of the different versions that resulted in the essay as we know it today. Among the various changes that the comparative reading identified, the swap of “saber” by “experimentar” is of the utmost relevance, as it sympathizes Borges practice with certain contributions of the literary theory put forward during the second part of the 20th century.Taking into account the aim and the theoretical contributions mentioned above, it was concluded that the destabilization of the notion of origin brings about productive outcomes that emphasize the essayistic writing maneuvers of Borges researched in this article and summarized in the final section.